Penyediaan Air Bersih Mandiri Permukiman Pesisir Kota Balikpapan berdasarkan Tingkatan Partisipasi - Mega Ulimaz; Risa Andini (JST (Jurnal Sains Terapan), 2018)
Kelurahan Baru Tengah is a sub-district in Kecamatan Balikpapan Barat which is the coastal area. This sub- district is dominated by settlement activities. Based on the Spatial Plan of Balikpapan City Year 2012-2032, the target of providing the needs of clean water of Balikpapan Barat reach 100% in 2030. However, Kelurahan Baru Tengah is an area that until now the providing of clean water needs has not been evenly distributed. In addition, there has been no guidance of community participation in the provision of clean water in this area. This study aims to formulate the guidance of the water supply community-based participation by using Analytical Hierarchy Process. The result of the analysis that has been done is the communities in Kelurahan Baru Tengah can participate at the level of Delegated Power in the form of their idea. The results obtained from this research are expected to be a reference for the provision of clean water in Kelurahan Baru Tengah which involves local community participation.Keywords : clean water provision, community participation, coastal area, analytical hierarchy process.